(untitled) (Third Sector Social Economic Review, 2022)
The relationship between health expenditures, environmental pollution and economic growth has recently become the focus of the literature. The aim of the study is to examine the effect of carbon emissions on health expenditures as an indicator of economic growth and environmental pollution in Turkey between 1980 and 2017. This study examines the relationship between health expenditures, economic growth and environmental pollution using the quantile regression method. When the empirical results of the study are examined, it allows us to see the effects of economic growth, CO2, old population (65+) and urbanization variables on health expenditures. Accordingly, it was concluded that economic growth increased health expenditures and carbon emissions increased health expenditures in low quantiles and decreased in medium-high quantiles. In addition, the old population was determined as the most important variable that increases health expenditures, and it was concluded that the amount of health expenditures increased as the old population increased. On the other hand, urbanization has been identified as another important factor that increases health expenditures. The causality results of the study show the existence of unidirectional causality from environmental pollution to health expenditures and from health expenditures to economic growth. It also shows the existence of a two-way relationship between the old population and urbanization and health expenditures. The findings of this study have determined that the growth hypothesis is valid for Turkey and that environmental degradation increases and decreases effects on health expenditures across quantiles. On the other hand, it has been concluded that economic growth provides an increase in health expenditures in the country in accordance with the conservation hypothesis.